2020
DOI: 10.1101/2020.06.29.179226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental models reveal the role of phenotypic plasticity in explaining genetic evolvability

Abstract: AbstractBiological evolution exhibits an extraordinary capability to adapt organisms to their environments. The explanation for this often takes for granted that random genetic variation produces at least some beneficial phenotypic variation for natural selection to act on. Such genetic evolvability could itself be a product of evolution, but it is widely acknowledged that the immediate selective gains of evolvability are small on short timescales. So how do biological systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…As a result, locally adapted phenotypes should resemble environmentally induced phenotypes, a pattern supported by a meta-analysis of reciprocal transplant experiments in plants ( Radersma et al, 2020 ). The phenotype dimensions that are adaptively plastic may in fact have particularly high evolvability since theoretical and empirical studies suggest that those dimensions harbour particularly high levels of additive genetic variation ( Draghi and Whitlock, 2012 ; Noble et al, 2019 ; Brun-Usan et al, 2020 ). Thus, all three conditions above are fulfilled, making plasticity appear to take the lead in adaptive evolution ( Kovaka, 2019 ; Uller et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, locally adapted phenotypes should resemble environmentally induced phenotypes, a pattern supported by a meta-analysis of reciprocal transplant experiments in plants ( Radersma et al, 2020 ). The phenotype dimensions that are adaptively plastic may in fact have particularly high evolvability since theoretical and empirical studies suggest that those dimensions harbour particularly high levels of additive genetic variation ( Draghi and Whitlock, 2012 ; Noble et al, 2019 ; Brun-Usan et al, 2020 ). Thus, all three conditions above are fulfilled, making plasticity appear to take the lead in adaptive evolution ( Kovaka, 2019 ; Uller et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plastic responses may constitute a relevant source of diversification and provide new possibilities for evolutionary processes (Gibson and Dworkin 2004; Brun‐Usan et al. 2020). Evaluation of hidden reaction norms ultimately fosters inference about evolutionary processes (Brun‐Usan et al.…”
Section: Figurementioning
confidence: 99%
“…Evaluation of hidden reaction norms ultimately fosters inference about evolutionary processes (Brun‐Usan et al. 2020).…”
Section: Figurementioning
confidence: 99%
“…Yet, the results are intelligible if evolution on the Greater Antilles had persistent effects on the lizards' developmental and behavioral biology, thereby imposing a bias on their future evolution following re-colonization of the mainland. Theoretical models of evolvability have demonstrated that strong selection for certain combinations of traits can promote the evolution of developmental interactions that make those traits vary together despite the genetic change being random [61][62][63] (reviewed in ref. 13 ).…”
Section: Discussionmentioning
confidence: 99%